2018
DOI: 10.1002/hep.29724
|View full text |Cite
|
Sign up to set email alerts
|

Current and future therapeutic regimens for nonalcoholic fatty liver disease and nonalcoholic steatohepatitis

Abstract: Over the next 5 years, some of these regimens are expected to provide potential new treatment options for patients with NASH/NAFLD. (Hepatology 2018;68:361-371).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
273
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 299 publications
(276 citation statements)
references
References 77 publications
(240 reference statements)
2
273
0
1
Order By: Relevance
“…A standardized assessment of the micro‐ and macrovascular complications of diabetes would be needed at inclusion and during regular follow‐up to help determine their relationship to the severity of NASH over time. Although some of this information is being gathered from the placebo arms of clinical trials on new NASH drugs, it is often not reported, or detailed information on diabetic complications is lacking . A study of this type would also provide long‐term information on the role of glycemic control, weight gain or weight loss over time, or that of other relevant factors.…”
Section: The Link Between Diabetes and Nash: Knowledge Gaps And Futurmentioning
confidence: 99%
“…A standardized assessment of the micro‐ and macrovascular complications of diabetes would be needed at inclusion and during regular follow‐up to help determine their relationship to the severity of NASH over time. Although some of this information is being gathered from the placebo arms of clinical trials on new NASH drugs, it is often not reported, or detailed information on diabetic complications is lacking . A study of this type would also provide long‐term information on the role of glycemic control, weight gain or weight loss over time, or that of other relevant factors.…”
Section: The Link Between Diabetes and Nash: Knowledge Gaps And Futurmentioning
confidence: 99%
“…There are no effective treatments for NASH beyond lifestyle modification with diet and exercise. However, clinical trials are in progress for agents designed to stop or reverse progression of NASH‐related fibrosis, by targeting pathways believed to be required for disease progression …”
Section: Clinical Burden Of Nafldmentioning
confidence: 99%
“…As new treatment regimens for NASH are developed, their effects on these outcomes must be demonstrated. The first important hurdle in clinical development of therapeutic agents for NASH is to improve patient outcomes . Although mortality is the ultimate clinical outcome, it is not a practical endpoint for clinical trials .…”
Section: Economic Outcomes Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations